Intervertebral Disk Degeneration: The Microenvironment and Tissue Engineering Strategies - Dou, Yiming; Sun, Xun; Ma, Xinlong; Zhao, Xin; Yang, Qiang (Frontiers in Bioengineering and Biotechnology, 2021)
Intervertebral disk degeneration (IVDD) is a leading cause of disability. The degeneration is inevitable, and the mechanisms are complex. Current therapeutic strategies mainly focus on the relief of symptoms, not the intrinsic regeneration of the intervertebral disk (IVD). Tissue engineering is a promising strategy for IVDD due to its ability to restore a healthy microenvironment and promote IVD regeneration. This review briefly summarizes the IVD anatomy and composition and then sets out elements of the microenvironment and the interactions. We rationalized different scaffolds based on tissue engineering strategies used recently. To fulfill the complete restoration of a healthy IVD microenvironment, we propose that various tissue engineering strategies should be combined and customized to create personalized therapeutic strategies for each individual.